Exploring service climate and employee performance in multicultural service settings - Fung, C.; Sharma, Piyush; Wu, Z.; Su, Y. (Emerald Group Publishing, 2017)
Purpose: The purpose of this paper is to introduce a new conceptual model that incorporates internal service quality as a mediator between service climate and employee performance and two personal cultural orientations (independence and interdependence) as the moderators of these relationships. Design/methodology/approach: An online survey of 353 employees representing 19 different nationalities, working in 18 branches and offices of a multinational business-to-business (B2B) civil engineering services firm, spread across 14 countries. Findings: All the hypotheses are supported. Specifically, internal service quality mediates the influence of service climate on employee performance and these relationships are stronger for employees with interdependent (vs independent) cultural orientations. Research limitations/implications: This paper uses data collected from the employees in a single B2B firm in one industry (Civil Engineering Services) and focuses on a few key variables, which may restrict the generalizability of its findings. Practical implications: The findings of this paper highlight the importance of cultural factors in building a service climate in multinational service organizations to help their employees work more effectively and efficiently with their colleagues from diverse cultural backgrounds. Originality/value: This paper clarifies the relationships among service climate, internal service quality and employee performance, by showing that internal service quality mediates the influence of service climate on employee performance.